Mucin adsorbed by E. coli can affect neutrophil activation in vitro. Issue 2 (19th December 2019) - Mikhalchik, Elena; Balabushevich, Nadezhda; Vakhrusheva, Tatiana; Sokolov, Alexey; Baykova, Julia; Rakitina, Daria; Scherbakov, Petr; Gusev, Sergey; Gusev, Alexander; Kharaeva, Zaira; Bukato, Olga; Pobeguts, Olga
Abstract : Bacteria colonizing human intestine adhere to the gut mucosa and avoid the innate immune system. We previously demonstrated that Escherichia coli isolates can adsorb mucin from a diluted solution in vitro . Here, we evaluated the effect of mucin adsorption by E. coli cells on neutrophil activation in vitro . Activation was evaluated based on the detection of reactive oxygen species production by a chemiluminescent reaction (ChL), observation of morphological alterations in neutrophils and detection of exocytosis of myeloperoxidase and lactoferrin. We report that mucin adsorbed by cells of SharL1 isolate from Crohn's disease patient's inflamed ileum suppressed the potential for the activation of neutrophils in whole blood. Also, the binding of plasma complement proteins and immunoglobulins to the bacteria was reduced. Desialylated mucin, despite having the same adsorption efficiency to bacteria, had no effect on the blood ChL response. The effect of mucin suggests that it shields epitopes that interact with neutrophils and plasma proteins on the bacterial outer membrane. Potential candidates for these epitopes were identified among the proteins within the bacterial outer membrane fraction by 2D‐PAGE, fluorescent mucin binding on a blot and HPLC‐MS/MS. In vitro, the following proteins demonstrated mucin adsorption: outer membrane porins (OmpA, OmpC, OmpD and OmpF), adhesin OmpX, the membrane assembly factor OmpW, cobalamine transporter, ferrum uptake protein and the elongation factor Ef Tu‐1. In addition to their other functions, these proteins are known to be bacterial surface antigens. Therefore, the shielding of epitopes by mucin may affect the dynamics and intensity of an immune response. Abstract : Escherichia coli isolates from healthy and inflamed intestines of humans adsorbed mucin from solution. Mucin adsorbed by cells of SharL1 isolate from Crohn's disease patient suppressed their potential for neutrophil activation and their ability to bind plasma complement proteins and immunoglobulins. OmpA, OmpC, OmpD, OmpF, OmpX, OmpW, cobalamine transporter, ferrum uptake protein and the Ef Tu‐1 bound mucin in vitro .